A functional and thromboelastometric-based micromethod for assessing crotoxin anticoagulant activity and antiserum relative potency against Crotalus durissus terrificus venom. (15th June 2018) - Prezoto, B.C.; Tanaka-Azevedo, A.M.; Marcelino, J.R.; Tashima, A.K.; Nishiduka, E.S.; Kapronezai, J.; Mota, J.O.; Rocha, M.M.T.; Serino-Silva, C.; Oguiura, N.
Abstract: The assessment of the capacity of antivenoms to neutralize the lethal activity of snake venoms still relies on traditional rodent in vivo lethality assay. ED50 and LD50 assays require large quantities of venoms and antivenoms, and besides leading to animal suffering. Therefore, in vitro tests should be introduced for assessing antivenom neutralizing capacity in intermediary steps of antivenom production. This task is facilitated when one key lethal toxin is identified. A good example is crotoxin, a β-neurotoxin phospholipase A2 -like toxin that presents anticoagulant activity in vitro and is responsible for the lethality of venoms of Crotalus durissus snakes. By using rotational thromboelastometry, we reported recently one sensitive coagulation assay for assessing relative potency of the anti-bothropic serum in neutralizing procoagulant activity of Bothrops jararaca venom upon recalcified factor-XII-deficient chicken plasma samples (CPS). In this study, we stablished conditions for determining relative potency of four batches of the anti-crotalic serum (ACS) (antagonist) in inactivating crotoxin anticoagulant activity in CPS (target) simultaneously treated with one classical activator of coagulation (agonists). The correlation coefficient (r) between values related the ACS potency in inactivating both in vitro crotoxin anticoagulant activity and the in vivo lethality of whole venom (ED50 ) was 0.94 (p value < 0.05). In conclusion, slowness in spontaneous thrombin/fibrin generation even after recalcification elicit time lapse sufficient for elaboration of one dose-response curve to pro- or anti-coagulant agonists in CPS. We propose this methodology as an alternative and sensitive assay for assessing antivenom neutralizing ability in plasma of immunized horses as well as for in-process quality control. Highlights: A new thromboelastometric-based micromethod suitable for accessing anticoagulant activity of toxins is proposed. Dose-response curve to coagulant agonists is easily performed on factor XII-deficient recalcified chicken plasma. Good correlation was observed between our in vitro micromethod and in vivo lethality neutralization by anticrotalic serum. This micromethod could be used to monitor antibody levels in horses during intermediate steps of antivenom production.